Etiological study of short stature in children and role of insulin like growth factor-1 and insulin like growth factor binding protein-3 as screening markers for growth hormone deficiency - Bibi, Afshan; Muhammad Aamir; Zujaja Hina Haroon; Umair Maqsood; Hajira; Uzma Qamar (Journal of the Pakistan Medical Association, 2023)
Objective: To determine aetiological factors in children with short stature, and to evaluate the role of insulin like growth factor-1 and insulin like growth factor binding protein-3 as screening markers for growth hormone deficiency. Method: The cross-sectional study was conducted at the Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from August 2020 to July 2021, and comprised children with short stature. Evaluation protocol included complete history and examination, baseline laboratory investigations, X-ray for bone age and karyotyping. Growth hormone status was assessed using growth hormone stimulation tests, and serum insulin like growth factor-1 and insulin like growth factor binding protein-3 levels were also assessed. Data was analysed using SPSS 25. Results: Of the 649 children, 422(65.9%) were boys and 227(34.9%) were girls. The overall median age was 11 years (interquartile range: 11 years). Of the total, 116(17.9%) children had growth hormone deficiency. Familial short stature was present in 130(20%) children and constitutional delay in growth and puberty in 104(16.1%). There was no significant difference in levels of serum insulin like growth factor-1 and insulin like growth factor binding protein-3 in children who had growth hormone deficiency and those who had other causes of short stature (p>0.05). Conclusion: Physiological variants of short stature were found to be more common in the population followed by growth hormone deficiency. Serum insulin like growth factor-1 and insulin like growth factor binding protein-3 levels alone should not be used to screen children with short stature for growth hormone deficiency. Key Words: Short stature, Growth hormone deficiency, Growth hormone stimulation tests, IGF-1, IGFBP-3.